2009
DOI: 10.1016/j.jpedsurg.2008.12.019
|View full text |Cite
|
Sign up to set email alerts
|

A prospective comparative evaluation of persistent respiratory morbidity in esophageal atresia and congenital diaphragmatic hernia survivors

Abstract: PurposeThe aim of the study was to compare long-term respiratory morbidity in children after repair of esophageal atresia (EA) or congenital diaphragmatic hernia (CDH). Patients and methodsChildren were seen at 6, 12, and 24 months and 5 years within a prospective longitudinal follow-up program in a tertiary children's hospital. Respiratory morbidity and physical condition were evaluated at all moments. At age 5 years, pulmonary function and maximal exercise performance were tested. ResultsIn 3 of 23 atresia p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 39 publications
10
82
0
1
Order By: Relevance
“…Recently, GISCHLER et al [24], from our group, evaluated maximal exercise performance in 16 5-yr-old children born …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, GISCHLER et al [24], from our group, evaluated maximal exercise performance in 16 5-yr-old children born …”
Section: Discussionmentioning
confidence: 99%
“…The mean SD-score for endurance time was -0.84 (also significantly different from zero, p50.012) [24]. In a study by PEETSOLD et al [25], 36 out of 53 survivors of CDH who had not received ECMO treatment (mean¡SD age 11.9¡3.5 yrs) reliably performed the Bruce treadmill test.…”
Section: Paediatric Lung Diseasementioning
confidence: 94%
“…As the traditional, mono-specialistic approach to children with congenital anomalies was felt to be inadequate, a multidisciplinary team and a multidisciplinary follow-up programme for these children and their parents were instituted in 1999. 7 …”
Section: Methods Settingmentioning
confidence: 99%
“…52,53)) fits the pattern of less conspicuous lung hypoplasia described in our study. In a parallel investigation of the long-term respiratory morbidity of EA-TEF and congenital diaphragmatic hernia survivors, it was demonstrated that 25% of cases in both groups had forced expiratory volume decreased by −2 z scores and that both had similar degrees of compromise of maximal exercise performance (54). Pulmonary hypoplasia persisting after the neonatal period will be a likely explanation.…”
Section: Lung Hypoplasia In Esophageal Atresiamentioning
confidence: 98%